Characterization of four varieties of Prunus L. from the Northern Iraq Region via phytochemical analysis using the GC-MS technique - NOOR AL-TALAB; SHAYMAA M. HISHAM; RAGHAD M. ABDULLA (Society for Indonesian Biodiversity, 2024)
Abstract. Al-Talab N, Hisham SM, Abdulla RM. 2024. Characterization of four varieties of Prunus L. from the Northern Iraq Region via phytochemical analysis using the GC-MS technique. Biodiversitas 25: 3712-3719. Prunus L. is a widely distributed fruit-producing plant cultivated since ancient times. Their morphology resembles most of the world's well-known temperate fruit crops, classified as pome and stone. This comprehensive study employed chemical taxonomic indicators to analyze distinct varieties within the Prunus L. genus, focussing specifically on Prunus armeniaca L. (represented by the Sayeb and Canion varieties) and Prunus domestica L. (represented by the Songold and Freedom varieties). The study then isolated and identified the active chemical compounds through Gas Chromatography-Mass Spectrometry (GC-MS) analysis. The findings showed that the Sayeb variety of P. armeniaca was found to have high concentrations of hexadecanoic acid (11.31), dl-phenylephrine (6.08), and 6-Bis-dimethylaminomethyl (3.00). Similarly, the Canyon variety of cultivar of P. armeniaca exhibited high concentrations of eucalyptol (46.35), hexadecanoic acid, methyl ester (13.21), and 11-octadecenoic acid (11.12). (46.35), hexadecanoic acid, methyl ester (13.21), and 11-octadecenoic acid (11.12).(46.35), hexadecanoic acid, methyl ester (13.21), and 11-octadecenoic acid (11.12). The Sungold variety of P. domestica was found to have sixteen compounds, with eucalyptol (40.72), alpha-pinene (9.64), and hexadecanoic acid, methyl ester (8.31) being the major compounds. The Freedom variety of P. domestica was also analyzed, with eucalyptol (50.36), ?-pinene (11.27), and hexadecanoic acid (9.76) identified as the major compounds. These distinct differences in chemical composition and abundance among different compounds provide valuable insights and open up exciting possibilities for their use as distinctive traits to determine diversity in the Prunus genus.